Students’ Perception of Using English Movies as Media for Increasing Idiomatic Expressions Acquisition - Dibyanti, Damara Dwi; Wahyuni, Sri (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study explores how students use idioms acquired from English movies to improve communication skills and how More Knowledgeable Other, henceforth mentioned as MKO, helped students comprehend the idioms. The Optimal Input Hypothesis by Krashen and Mason (2020) and the Sociocultural Theory by Vygotsky (1978) were the theoretical basis for conducting the research. The survey was conducted using an open-ended questionnaire distributed online to UNNES' English Literature and English Education students who enjoy watching English movies and have passed Idiom-Based Lexical Studies course. The thematic analysis method proposed by Braun and Clarke (2006) was used to analyze the collected data. The result of the study shows that most of the participants agree that English movies help them acquire more idiomatic expressions supported by human and technological scaffolding. Participants also shared that the idiomatic expressions acquired from English movies improve their communication and writing skills. This research reveals that giving more input from English movies encourages students to use idioms in both spoken and written expressions. In addition, MKOs play roles in supporting students' process of understanding idiomatic expressions acquired from English movies, and the more preferred one is technology MKO.